Effects of dual-alcohol gasoline blends on physiochemical properties and volatility behavior. (15th September 2019) - Aghahossein Shirazi, Saeid; Abdollahipoor, Bahareh; Martinson, Jake; Windom, Bret; Foust, Thomas D.; Reardon, Kenneth F.
Highlights: Dual alcohol blends reduce the limitations of single-alcohol blends. Dual-alcohol blends can be designed to have vapor pressures similar to gasoline. The dual-alcohol approach can improve volatility, viscosity, and water tolerance. The dual-alcohol approach can increase the use of biofuel in the current system. 3-Methyl-3-pentanol has promising fuel properties to be used as a blendstock. Abstract: Biofuels can contribute to reducing greenhouse gas emissions from the transportation sector. Ethanol is the main additive for gasoline in the United States, and gasoline containing 10 vol% ethanol is the most commonly used transportation fuel. However, the vapor pressure of these blends is significantly higher than gasoline, which contributes to evaporative emissions. One way to circumvent this and other issues is to use a dual-alcohol approach, mixing lower (methanol or ethanol) and higher alcohols with gasoline to obtain a blend with a vapor pressure close to that of the base gasoline. The goal of this study was to evaluate the fuel potential of dual alcohol blends experimentally and theoretically. Ten dual-alcohol blends were tested at blending ratios from 10 to 80 vol%, with methanol and ethanol used as the lower alcohols and iso-butanol and 3-methyl-3-pentanol as the higher alcohols. The corresponding single alcohol-gasoline blends were also evaluated. For each blend, Reid vapor pressure, vapor lock protection potential, distillation curve, lower heating value, kinematic viscosity, and water tolerance at three temperatures were measured. A model of droplet evaporation was also applied to provide insights into the azeotropic volatility behavior and mixing/sooting potential of the blends. The results of this study show that it is advantageous to use dual-alcohol blends containing up to 40 vol% because they have the characteristics necessary for good performance in existing spark-ignition engines, particularly in terms of volatility, kinematic viscosity, and water tolerance. This study is the first to characterize matched vapor pressure, dual-alcohol blends over a wide blending range as drop-in fuels for conventional spark ignition engines. Furthermore, this was the first investigation of the fuel potential of iso-butanol in dual-alcohol blends and of 3-methyl-3-pentanol in single- and dual-alcohol blends.